2005
DOI: 10.1295/polymj.37.571
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Bile Salts to an Amphiphilic Polysulfonate Modified with Cholesterol Moieties

Abstract: ABSTRACT:A hydrophobically modified polysulfonate bearing a small mole percent (5 mol %) of cholesteryl moieties forms an intermolecularly bridged flower micelle in water, arising from intermolecular associations of the polymer-bound cholesteryl groups. Binding of sodium cholate (SC) to this polymer micelle in water was investigated using 1 H NMR spin-spin relaxation time, static light scattering, quasi-elastic light scattering, and fluorescence techniques. The intermolecular association of the polymer-bound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…49 Other applications of copolymers bearing cholesterol side-chains include optical data recording and storage 15,18,[50][51][52] and solution self-assembled fluorescent probes. [53][54][55][56][57][58] Many of the examples noted earlier comprise random copolymers with main and side-chain cholesterol units. However, we are interested in synthesizing well-defined block copolymers comprising side-chain cholesterol units in one block and moieties capable of hydrogen bonding in the second block.…”
Section: Introductionmentioning
confidence: 99%
“…49 Other applications of copolymers bearing cholesterol side-chains include optical data recording and storage 15,18,[50][51][52] and solution self-assembled fluorescent probes. [53][54][55][56][57][58] Many of the examples noted earlier comprise random copolymers with main and side-chain cholesterol units. However, we are interested in synthesizing well-defined block copolymers comprising side-chain cholesterol units in one block and moieties capable of hydrogen bonding in the second block.…”
Section: Introductionmentioning
confidence: 99%
“…mc X mc f [13] As said by the pseudo phase separation model, [42] the standard Gibbs energy of micellization ( 0 m ΔG ), for PMZ and bile salts as well as their mixtures can be evaluated by taking into consideration the degree of dissociation (g) of the counter ion to the micelle 0 m ΔG = (2 g) RT lnX cmc [14] where X cmc , g, R and T are the cmc expressed in mole fraction units, degree of dissociation, gas constant and temperature, respectively. The non-ideality in the mixed micelle due to interaction can be assessed by evaluating molar excess standard free energy of micellization ( ex G ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…)-(13). Activity coefficients evaluated by various recommended models, are less than unity at all 1 and temperatures which point out attractive nonideal behavior of the mixed systems; however, differences between the activity coefficient suggest significant role of entropy in mixing of amphiphiles(Tables 1-2).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…However, this method is not useful for the polymerization of methacrylic acid or acrylic acid monomers, because such systems need basic ligands such as bipyridyl compounds. The RAFT process is also a convenient method for the architecture of hydrophilic polymers using water‐soluble chain transfer reagents such as 4‐cyanopentanoic acid dithiobenzoate 14–16. More recently, we demonstrated that density functional theory calculations provide a reliable and quantitative prediction of the trends in C‐S bond dissociation energies for several model compounds as photoinitiator.…”
Section: Introductionmentioning
confidence: 99%